2002
DOI: 10.1081/pfc-120003097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Organic Matter on the Leaching of Polycyclic Aromatic Hydrocarbons in Soil

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are one of the main classes of contaminants in the terrestrial environment. Aside from total organic carbon, the ratio among the different organic matter fractions [dissolved organic matter, fulvic acid (FA), humic acid (HA) and humin] can also affect the mobility of these hydrocarbons in soils. In this study the effect of the whole organic carbon pool has been compared with that of HA and FA on the translocation of four PAHs (biphenyl, fluorene, phenanthrene and pyrene)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…The type of organic matter fraction that PAHs are connected with affects their mobility in the soil profile. Humic acids limit the mobility of hydrocarbons deep down in the soil profile, whereas fulvic acids stimulate that process (Petruzzelli et al 2002). As was reported by Kim and Kwon (2010), the sorption properties of humic acids towards PAHs increase with an increase in the PAHs hydrophobicity.…”
Section: Introductionsupporting
confidence: 55%
“…The type of organic matter fraction that PAHs are connected with affects their mobility in the soil profile. Humic acids limit the mobility of hydrocarbons deep down in the soil profile, whereas fulvic acids stimulate that process (Petruzzelli et al 2002). As was reported by Kim and Kwon (2010), the sorption properties of humic acids towards PAHs increase with an increase in the PAHs hydrophobicity.…”
Section: Introductionsupporting
confidence: 55%
“…An increase in the PAH content from the outset of the present experiment was related to soil type. Numerous authors (Maliszewska-Kordybach, 1995;Oleszczuk & Baran, 2005;Petruzzelli et al, 2002;Pignatello & Xing, 1996) showed a significant influence of the soil characteristics on the fate of polycyclic aromatic hydrocarbons. As has been mentioned earlier, soil B was characterized by an organic carbon content several times higher.…”
Section: Discussionmentioning
confidence: 98%
“…According to available information, there has not been any model studies on the influence of long-term soil flooding on the changes in the levels of polycyclic aromatic hydrocarbons carried out so far. The existing experiments were limited to soil leaching with water in order to determine potential migration of this type of xenobiotics deeper into the soil profile (Kim & Osako, 2003;Petruzzelli, Celi, Cignetti, & Marsan, 2002;Weigand et al, 2002) and to monitor changes in the PAH content in relation to soil humidity level (Hesina, Krivosejeva, Vorobieva, & Stepanova, 1987;Maliszewska-Kordybach, 1995). Despite hydrophobic properties of most PAHs their solubility in water can be increased as a result of presence of surfactants (Cesare & Smith, 1994), soil colloids (Mccarthy & Zachara, 1989) and dissolved organic carbon (Kögel-Knabner & Totsche, 1998;Magee, Lion, & Lemley, 1991) in the soil (soil solution).…”
Section: Discussionmentioning
confidence: 99%
“…Chiou et al, 1998;Northcott and Jones, 2001) whereas column leaching methods accompanied by analysis of both the leachates and the soil column permit simulation of the downward soil movement of contaminants (Jackson et al, 1984). Similar experiments have identified the important role played by the quantity and quality of soil organic matter in controlling the leaching of PAHs from soils and sediments (Petruzelli et al, 2002;Ran et al, 2007). Other controlling factors influencing the PAH leaching potential include the soil water ratio (Enell et al, 2004;Zand et al, 2010), residence time (Weigand et al, 2002), temperature (Enell et al, 2005), soil grain size (Zhang et al, 2008), soil aging (de Jonge, 2008), ionic strength of the leachate (Kim and Osako, 2003) and surfactant addition to the leachate (Frutos et al, 2011;Ganeshalingam et al, 1994).…”
Section: Introductionmentioning
confidence: 92%
“…Jones et al (1989) found that PAH leaching rates were strongly influenced by the existence of DOC mediated or particle associated transport and Petruzelli et al (2002) have identified the different roles played by humic and fulvic acids in controlling the vertical leaching of PAHs with the former enhancing retention whereas fulvic acids favoured an increase in PAH mobility. For the PAHs recovered at levels greater than 50% (i.e.…”
Section: Soil Depth Penetrationmentioning
confidence: 99%